Sexual and Reproductive Health Among Women with Disabilities in Kailali District - Karki, Lal Singh (Exploration अन्वेषण, 2026)
The study aims to identify the demographic and socio-economic characteristics of women with disabilities, assess their knowledge, attitudes and practices about sexual and reproductive health and examine their sexual and reproductive health-related problems. A descriptive research design was adopted for using primary and secondary data sources. Primary data were collected using structured interviews with 40 women with disabilities in Janaki Rural Municipality, Kailali District, and secondary data were collected from municipal records and reports of concerned NGOs. The findings reveal that most of the respondents were Hindus. They were also housewives, and more than half of them belonged to nuclear family units. Sexual and reproductive health knowledge of respondents came from school/college, training and other interpersonal communication. In terms of menstrual hygiene, 50 percent of respondents used cloth, and a few used sanitary pads, homemade pads, and other materials. Over 20 percent of respondents slept separately during the period of menstruation. Most respondents received antenatal checkup services. The main reasons for not accessing antenatal services are attributed to a lack of knowledge, a shortage of time, the absence of services, and fear. Concerning family planning, the majority of respondents used condoms, and some others used injectable and other methods. Concerning the vaccination and delivery practices, most of the respondents reported having received the T. T. vaccine and having taken iron tablets. The majority of respondents reported having given birth in a hospital. They reported several sexual and reproductive health problems. These included abdominal pain, vaginal bleeding, vomiting, headaches, irregular menstruation, difficulty keeping clean, postpartum depression, lack of health services and other health problems. The study recommends that improving literacy and income, and implementing community participatory health programs, taking into account cultural beliefs, family support, and community the focus on promoting sexual and reproductive health for women with disabilities.